Moose Movement and Habitat Use in Old Crow Flats, 2007-2009 - Nagwan, Lance; Cooley, Dorothy; Humphries, Murray (Canadian Cryospheric Information Network, 2012)
Current knowledge of moose migration in this region is limited to the observation that a majority of moose captured in northeastern Alaska migrate almost 200 kilometers to spend the summer in the OCF. We will capture 10 cow and 9 bull moose on the OCF in 2007-08 and fit them with satellite download GPS collars. These will provide two years of data on the seasonal and annual home ranges of collared moose, which will be related to vegetation and hydrological conditions using a resource selection function approach. Standard morphological measurements and blood, fecal, and hair samples collected during captures will provide necessary baseline data on the biology of moose inhabiting the OCF. Subsequent community-based monitoring of moose abundance and habitat use within the OCF will involve harvest surveys, moose browse and scat surveys, and occasional aerial surveys. : Purpose: This initiative will examine how moose habitat use within the OCF is related to variation in microclimate, hydrology, and shrub distribution, as well as the timing and spatial extent of moose migration. : Summary: As browsers of shrubby vegetation, moose are frequently found beyond the northern forest limit in localized areas of abundant shrub growth, frequently adjacent to rivers and lakes. Moose populations appear to be increasing in the OCF, as well as many other localities within Canada's forest-tundra transition. The increase in moose populations near the northern periphery of their range is frequently attributed to increased shrub growth resulting from climate change, but data linking moose abundance and space use to the distribution of shrubs are scarce, particularly within the forest-tundra transition zone.